2021
DOI: 10.3390/agronomy11050891
|View full text |Cite
|
Sign up to set email alerts
|

Development of Extra-Early Provitamin A Quality Protein Maize Inbreds with Resistance/Tolerance to Striga hermonthica and Soil Nitrogen Stress

Abstract: A hemiparasitic plant, Striga hermonthica (Del.) Benth and soil nitrogen stress are the key constraints to maize (Zea mays L.) productivity in sub-Saharan Africa, where commonly cultivated maize is the normal endosperm type that is deficient in provitamin A, tryptophan and lysine (PVATL). Seventy-six extra-early maize inbreds with provitamin A, tryptophan, and lysine qualities (TZEEIORQ) were developed to address these constraints, and four checks were assessed under Striga, low and high nitrogen conditions at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…These results are similar with the findings of Konaté et al (2017) who reported the lack of significant G×E for Striga damage ratings at 8 and 10 WAP. In previous studies significant G×E have reported for Striga damage ratings at 8 and 10 WAP and grain yield related traits (Makumbi et al,2015;Kanampiu et al,2018;Oyekale et al,2021). The difference in the results of this study and those of the previous authors suggests that the environments where the genotypes have been evaluated, and their genetic background might be different.…”
Section: Discussioncontrasting
confidence: 85%
“…These results are similar with the findings of Konaté et al (2017) who reported the lack of significant G×E for Striga damage ratings at 8 and 10 WAP. In previous studies significant G×E have reported for Striga damage ratings at 8 and 10 WAP and grain yield related traits (Makumbi et al,2015;Kanampiu et al,2018;Oyekale et al,2021). The difference in the results of this study and those of the previous authors suggests that the environments where the genotypes have been evaluated, and their genetic background might be different.…”
Section: Discussioncontrasting
confidence: 85%
“…There is consistently strong evidence ( 34 ) that strategically increasing plant diversity increases crop and forage yield, wood production, yield stability, pollinators, weed suppression, and pest suppression. An example of successful application of crop genetic diversity to enhance yield stability in a tropical context is seen in Nigeria where the recent development of super-sweet maize hybrids ( 35 ) as well as provitamin A quality protein maize ( 36 ) have potential to diversify the maize value chain. This chain was previously dominated by flint and dent endosperm types and this offers some diversity in nutrition and business opportunities.…”
Section: Transforming Urban Food Systems Through Sustainable One Heal...mentioning
confidence: 99%
“…The majority of resource-poor families in sub-Saharan Africa (SSA) consume conventional maize that were deficient in major nutrients such as provitamin A (PVA) carotenoids and amino acids (lysine and tryptophan) (Oyekale et al 2021). Such diets are fed to infants (from 2-3 months old) and babies of preschool age without nutritional supplements in several developing countries (Badu-Apraku et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tryptophan and lysine amino acids are major protein building blocks needed by monogastric animals and humans (Oyekale et al 2021). A deficiency of tryptophan resulted in increased pain sensitivity, impaired bone development, a decline in growth rate, lessened food intake, increased aggression, and nervousness (Moehn et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation